Analysis of the Impact of Modern Livestock Technology Implementation, Resource Availability, and Marketing Strategy on the Sustainability of Chicken Farming Business in Central Java - Frans Sudirjo; Josua Sahala; Zainal Abidin; Andi Sabirin Baso; Sainul Hamid (Westscience Press, 2023)
This research investigates the key determinants of sustainability in the chicken farming industry, focusing on the interplay between marketing strategy, modern livestock technology implementation, resource availability, and the overall sustainability of chicken farming businesses. Utilizing Structural Equation Modeling (SEM), data from a sample of chicken farmers in the study region were analyzed to assess the relationships among these variables. The results highlight the significant positive impacts of a well-executed marketing strategy, adoption of modern livestock technology, and resource availability on the sustainability of chicken farming operations. The findings provide actionable insights for industry stakeholders to enhance their strategies and practices, contributing to a more sustainable and resilient chicken farming sector.